Biografi mufti-mufti Malaysia - Azman AB Rahman; Universiti Sains Islam Malaysia (Nilai, Negeri Sembilan : Penerbit Universiti Sains Islam Malaysia, 2008)
Biography of Malaysian muftis.
Keywords: Muftis (Muslim officioals) -- Malaysia -- Biography